Down-Regulated FOXO1 in Refractory/Relapse Childhood B-Cell Acute Lymphoblastic Leukemia - Zheng, Qingqing; Jiang, Chuang; Liu, Haiyan; Hao, Wenge; Wang, Pengfei; Huang, Haiying; Li, Ziping; Qian, Jiabi; Qian, Maoxiang; Zhang, Hui (Frontiers in Oncology, 2020)
Background Acute lymphoblastic leukemia (ALL) is the most common pediatric cancer, with an overall prevalence of 4/100,000, accounting for 25-30% of all childhood cancers. With advances in childhood ALL treatment, the cure rate for childhood ALL has exceeded 80% in most countries. However, refractory/relapsed ALL remains a leading cause of treatment failure and subsequent death. Forkhead box O1 (FOXO1) belongs to the forkhead family of transcription factors, but its role in B-cell ALL (B-ALL) has not been determined yet. Procedures RNA sequencing was applied to an ALL case with induction failure to identify possible genetic events. A cytokine-dependent growth assay in Ba/F3 cells was used to test the leukemic transformation capacity of MEIS1-FOXO1. The propidium iodide (PI) staining method was used to evaluate the effect of MEIS1-FOXO1 on cycle distribution. FOXO1 transactivity was examined using a luciferase reporter assay. FOXO1 mRNA expression levels were examined using real-time quantitative PCR among 40 children with B-ALL treated with the CCCG-ALL-2015 protocol. Association analysis was performed to test the correlation of FOXO1 transcription with childhood B-ALL prognosis and relapse in a series of GEO datasets. An MTT assay was performed to test the drug sensitivity. Results In this ALL case with induction failure, we identified a novel MEIS1-FOXO1 fusion gene. The transactivity of MEIS1-FOXO1 was significantly lower than that of wild-type FOXO1. MEIS1-FOXO1 potentiated leukemia transformation and promoted Ba/F3 cell cycle S-phase entry. Low FOXO1 transcription levels were found to be strongly associated with unfavorable ALL subtype, MRD positivity, and relapse. Lower FOXO1 expression was associated with prednisone and cyclophosphamide resistance. Conclusions Low FOXO1 transcription was associated with high-risk stratification and relapse in children with B-ALL, probably due to multi-drug resistance.